Ungkapan Kemarahan Masyarakat Etnis Pasemah Bengkulu: Kajian Tradisi Lisan Sebagai Sarana Kontrol Sosial - Fitra Youpika; Tedi Permadi; Sumiyadi Sumiyadi; Dadang Sunendar (Universitas Andalas, 2023)
This research is a study of cultural expressions (oral traditions) which aims to describe traditional expressions of the Pasemah Bengkulu ethnicity as a means of social control in society. The research method used is a descriptive ethnographic approach. The research data is in the form of traditional expressions of the Pasemah Bengkulu ethnic community which were obtained through observation and or recording from a number of informants intentionally or not. The research procedure follows the steps proposed by Spradley (1997). The results of the study are seen from the meaning, communication situations, speakers of the other party, and ways of expressing anger. Expression of anger is a means to express feelings of annoyance, disappointment, and dislike. Expressions of anger can be a means of therapy for speakers and interlocutors for the emotions they experience and are one of the cultural images of the Pasemah Bengkulu ethnic community. In addition, the expression of anger is also a form of social control for society as well as a recorder of taboo vocabulary.